Profiling the Properties of SILAR Synthesized MnSe Films as Potential Material for Absorber Layer of Thin Film Solar Cells - Asielue O Kingsley; Opene J Nkechi; Okoli N Livinus (Physics Access)
This study investigates the optical, structural, and electrical properties of manganese selenide (MnSe) thin films synthesized using the Successive Ionic Layer Adsorption and Reaction (SILAR) method, with varying volumes of triethylamine (TEA) as a complexing agent. The MnSe films exhibited high absorbance in the ultraviolet (UV) region, peaking at values from 0.61 to 0.91 depending on TEA concentration, and declining towards the near-infrared (NIR) region. Transmittance varied from 12.53% to 92.17%, decreasing with higher TEA concentrations. The energy band gap of the films decreased from 2.90 eV with 2 ml of TEA to 2.30 eV with 10 ml, highlighting the tunability of MnSe for photovoltaic applications. Film thickness varied from 190.82 nm to 381.63 nm, reflecting a direct relationship with TEA concentration. Structurally, the MnSe films crystallized in the cubic phase with improved crystallinity and reduced defects at higher TEA volumes, as evidenced by a crystallite size increase from 20.10 nm to 25.09 nm and decreased dislocation density and microstrain. Morphological analysis revealed uniform grain-like structures at moderate TEA concentrations, which are optimal for photovoltaic performance. The electrical properties highlighted a trade-off between resistivity and conductivity. Films deposited with lower TEA volumes exhibited higher electrical conductivity of 2.72 × 10ିହ S/cm at 2 ml compared to 1.02 × 10ିହ S/cm at 10 ml. These findings confirm the suitability of MnSe thin films for absorber layers in solar cells, particularly where tunable optical and electrical properties are desired. The ability to control these properties by varying TEA concentration enhances the material's versatility for applications beyond photovoltaics, including optoelectronic and photodetector devices.